Clinical-epidemiological characterization of COVID 19. MICONS Isolation Center. Cienfuegos, 2021 - Juan Rafael Zerquera Rodriguez; Livan Rojas Lantigua; Bárbaro Orlando Pérez Sabina; César Coma García; Keyla Zerquera Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: the COVID-19 pandemic has had a considerable impact in terms of infections, deaths, economic and social changes in the world. Objective: to characterize the suspected and confirmed cases of COVID19 in the MICONS Isolation Center in Cienfuegos. Methods: Observational, descriptive cross-sectional study that included the total number of suspected (836) and confirmed (193) cases reported with COVID-19 in the study period. Clinical and epidemiological records of the cases were reviewed. The variables analyzed were age, sex, municipality of origin, occupation, source of infection, comorbidity, symptoms presented, positive and negative rapid tests, positive and negative PCR, type of case and statistical week. Results: the age group between 45 and 59 years old prevailed with 33.8%; 48.4% of patients admitted to the center were hypertensive; 23.4% of the total cases were positive for the SARS-CoV-2 virus; the predominant symptoms were fever with 39.2%; cough with 37.7% and headache with 30.1%. Conclusions: the work responds to a scientifically based vision of the characteristics of the COVID -19 pandemic in the province in terms of the form of control, where it is necessary to continue carrying out new studies to evaluate the impact of this disease in public health.